Developing speaking materials for students of Mechanical Engineering at State Polytechnic of Malang - Achmad Sjaifullah (Jurnal Linguistik Terapan, 2011)
Developing teaching materials for the students of Mechanical Engineering of State Polytechnic of Malang is urgently needed by considering the fact that no such representative suitable material is available. For the time being, the teaching of speaking class in the Mechanical Engineering greatly depends on the commercial text books, the contents of which are mostly not always in line with communicative contexts of the Mechanical Engineering. The research findings show that: (1) there are five aspects to be included in the developed materials, these are: the aim, the topic, the organization and design, the language, and the exercises. (2) Based on the evaluation from the experts, the lecturers and the students, this developed student book is considered appropriate for further use in the speaking class. At last, this developed student book is considered suitable and applicable because it contains basic concepts required in the speaking skill and simple exercises. The results of the try‐out become clear evidence for the aforementioned suitability and applicability.